Why Does Momentum Persist? - Samsa, Greg (Archives of Business Research, 2020)
The phenomenon of short-term momentum in intriguing because it directly contradicts the notion that in an efficient market stock prices should lack memory. Three classes of possible explanation for momentum are (1) it is consistent with tenets of efficient markets after appropriate risk adjustment; (2) it is consistent with tenets of behavioral finance because of investors' cognitive biases; and (3) it is consistent with structurally-based positive feedback loops. The presence of extreme bubbles provides evidence against the first explanation. The fact that prices are effectively set by institutional investors who are aware of the cognitive biases in question and have a financial incentive to avoid them provides evidence against the second. Structurally-based explanations include the short-term incentives of institutional money managers and the impact of indexing. We believe that considering structural factors affecting the behavior of stock prices provides an additional perspective, to be used in combination with behavioral finance and market efficiency.